Cybersecurity and Digital Inclusion Through the Prism of Ensuring Access to Information and Protection of Fundamental Freedoms - Bernik, Igor (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
Cyber security and digital inclusion play a crucial role in achieving sustainable development and building inclusive societies in a digital society. The 16th Sustainable Development Goal of the United Nations calls for providing public access to information and protecting fundamental freedoms following national legislation and international agreements. The paper discusses the importance of cyber security in protecting digital infrastructure, which is the key to secure and free access to information. It also highlights the role of digital inclusion in reducing the digital divide and ensuring equal opportunities for all. Examples of good practices from different countries that have successfully implemented policies to improve cyber security and digital inclusion are presented, emphasising their contribution to the achievement of United Nations Goal 16. The paper contributes to understanding how local and national initiatives can work together to strengthen inclusive and safe digital environments as a foundation for sustainable development.